2014
DOI: 10.1134/s1063785014120244
|View full text |Cite
|
Sign up to set email alerts
|

Selection of boundary conditions for modeling thermowave processes in multilayer objects

Abstract: Solution of many problems related to the heat transfer involves the calculation or determination of the influence of interfaces between two or more neigh boring regions. Possible applications of this vary from fundamental investigations in nanophysics to practi cally important calculations of heat transfer in high power electronics and construction engineering. A standard approach to solution of these problems consists in replacing the boundary layer of finite thick ness by a negligibly thin layer with finite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…This situation can be illustrated by the example of the simplest structure shown in Figure 2 . Using the concept of incident and reflected thermal waves and following the approach developed in [ 57 , 58 ], the alternative temperature components for three regions can be presented in the form of plane waves where x is the coordinate shown in Figure 2 , t is the time, l is the thickness of the second layer, q n were obtained from the heat equations for each layer and q n = (−1 + i ) ( ω /2 κ n ) 1/2 , ω is the cyclic frequency of thermal waves, κ n is the thermal diffusivity of the n th layer, a is the amplitude of the incident thermal wave, and r , b , c , τ are coefficients to be determined from boundary conditions.…”
Section: Theoretical Model For Evaluation Of Thermal Properties Of Mu...mentioning
confidence: 99%
See 2 more Smart Citations
“…This situation can be illustrated by the example of the simplest structure shown in Figure 2 . Using the concept of incident and reflected thermal waves and following the approach developed in [ 57 , 58 ], the alternative temperature components for three regions can be presented in the form of plane waves where x is the coordinate shown in Figure 2 , t is the time, l is the thickness of the second layer, q n were obtained from the heat equations for each layer and q n = (−1 + i ) ( ω /2 κ n ) 1/2 , ω is the cyclic frequency of thermal waves, κ n is the thermal diffusivity of the n th layer, a is the amplitude of the incident thermal wave, and r , b , c , τ are coefficients to be determined from boundary conditions.…”
Section: Theoretical Model For Evaluation Of Thermal Properties Of Mu...mentioning
confidence: 99%
“…In [ 57 , 58 ], the coefficients at the exponents r , c , d , and τ as functions of the wave amplitude a were found in the analytical form by solving the heat equations for the structure shown in Figure 2 with common boundary conditions representing the continuity of temperature and heat flux at interfaces. In these publications, it was shown that in the case of a thin intermediate layer, the thermal problem for the structure in Figure 2 can be reduced to the problem of two regions between which there is the real TR r th and the reactive thermal conductance of the capacitive type z th where K 2 and ρ 2 C 2 are the thermal conductivity and the volumetric heat capacity of the intermediate layer, respectively, and i is the imaginary unit.…”
Section: Theoretical Model For Evaluation Of Thermal Properties Of Mu...mentioning
confidence: 99%
See 1 more Smart Citation
“…It was also demonstrated in [7] that a change in the solder composition induces considerable variations of its thermal conductivity and thermal capacity. The latter factor may be taken into account by introducing thermal impedance [15] into the boundary condition for heat fluxes. In the discussed case of lead-free solder pastes, it was also needed to introduce a similar parameter into the Ge substrate-solder layer boundary condition to characterize the PD signal accurately.…”
mentioning
confidence: 99%